1997
DOI: 10.1139/v97-115
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective intramolecular annulation of 3-alkylindolines into dihydro or tetrahydrofuro[2,3-b]indoles

Abstract: 3-Alkyl-2-hydroxyindolines, conveniently prepared from 2-hydroxyindolenines and a Grignard reagent, cyclize in the aprotic solvent tetrahydrofuran to afford tetrahydro-3-cyano-2-oxofuro[2,3-b]indoles, while in the protic solvent methanol the chemoselectivity changed to give dihydro-2-amino-3-carbomethoxyfuro[2,3-b]indoles. The steric effect of the alkyl group on the reactivity of 3-alkyl-2-hydroxyindolines is discussed for both processes. The ring transformation of tetrahydro-3-cyano-2-oxofuro[2,3-b]indoles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…On the basis of these results, we propose the carbamic acid structures 6 and 7 for the two transient intermediates (Chart ). It has been reported that the chemical shifts of carbonyls in compounds with similar CNCOO structures are above 161 ppm and the chemical shifts of carbonyls in compounds with NHCOO structures are ∼150 ppm (Chart ), which correlate very well with our structure assignments. Compounds 6 and 7 readily decompose to form 5 and CO 2 .…”
Section: Discussionsupporting
confidence: 85%
“…On the basis of these results, we propose the carbamic acid structures 6 and 7 for the two transient intermediates (Chart ). It has been reported that the chemical shifts of carbonyls in compounds with similar CNCOO structures are above 161 ppm and the chemical shifts of carbonyls in compounds with NHCOO structures are ∼150 ppm (Chart ), which correlate very well with our structure assignments. Compounds 6 and 7 readily decompose to form 5 and CO 2 .…”
Section: Discussionsupporting
confidence: 85%
“…Melting points were determined on a Fisher-Johns apparatus and are uncorrected. IR spectra were obtained using a Perkin-Elmer 16F PC spectrophotometer, 1 H and 13 C NMR spectra on a Varian XL300GS spectrometer working at 300 and 75.4 MHz, respectively. All chemical shifts are reported in δ units relative to TMS.…”
Section: Experimental Generalmentioning
confidence: 99%
“…Column chromatography was performed on Silica Gel 60 (230–400 mesh) from Aldrich. Ketene acetals 1a, 1b, 2a and 2b and 2‐indolyl cyanomalonates 4a – e were synthesized as described8 from the corresponding methyl 3‐cyano‐3a‐alkyl‐2‐oxo‐2,3,3a,8a‐tetrahydro‐8 H ‐furo[2,3‐ b ]indole‐8‐carboxylates 8, 19, 20…”
Section: Methodsmentioning
confidence: 99%